TEACHERS’ PERCEPTIONS OF USING AI IN ENGLISH LANGUAGE TEACHING - Akramova Muattar Bakhodirovna (International Journal of Literature and Language Studies, 2026)
Artificial Intelligence (AI) has rapidly emerged as a transformative technology in education, particularly in English Language Teaching (ELT). AI-powered applications such as ChatGPT, Grammarly, Duolingo, QuillBot, and automated assessment systems have significantly influenced language teaching practices by enhancing lesson preparation, providing personalized learning experiences, and facilitating immediate feedback. Despite these advantages, teachers remain central to the successful implementation of AI in language education. This article explores English language teachers' perceptions of using AI in ELT by examining its pedagogical benefits, challenges, and implications for classroom practice. A review of recent literature indicates that teachers generally perceive AI as a valuable instructional tool that enhances teaching efficiency, learner engagement, and individualized instruction. However, concerns persist regarding academic integrity, overreliance on AI-generated content, data privacy, ethical considerations, and the lack of sufficient technological competence among educators. The study also highlights the importance of professional development and institutional support in promoting teachers' AI literacy and responsible AI integration.